2015
DOI: 10.1111/crj.12353
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone propionate in clinically suspected asthma patients with negative methacholine challenge test

Abstract: A significant portion of CSA/MCT- (especially those with pretreatment ACT score <15) respond to high dose fluticasone inhaler in terms of symptoms relief, disappearance of wheeze and need to bronchodilator use. ΔACT could not be predicted with any individual symptoms or signs before MCT, % FEV1 decline or symptoms during MCT and exhaled nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In one study, Khalid et al found that 15 of 77 methacholine non‐responders presenting asthma‐like symptoms developed overt asthma over a 3‐yr period; noticeably, 43% of patients with 10%‐20% decline in FEV1 during the MCT eventually developed asthma. More recently, Peiman et al reported a marked improvement in asthma symptoms and the disappearance of wheeze in methacholine non‐responders with clinically suspected asthma receiving treatment with high doses of inhaled fluticasone. However, as acknowledged by the respective authors, the above studies were somehow limited either by their retrospective design or by the lack of a control group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, Khalid et al found that 15 of 77 methacholine non‐responders presenting asthma‐like symptoms developed overt asthma over a 3‐yr period; noticeably, 43% of patients with 10%‐20% decline in FEV1 during the MCT eventually developed asthma. More recently, Peiman et al reported a marked improvement in asthma symptoms and the disappearance of wheeze in methacholine non‐responders with clinically suspected asthma receiving treatment with high doses of inhaled fluticasone. However, as acknowledged by the respective authors, the above studies were somehow limited either by their retrospective design or by the lack of a control group .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Peiman et al reported a marked improvement in asthma symptoms and the disappearance of wheeze in methacholine non‐responders with clinically suspected asthma receiving treatment with high doses of inhaled fluticasone. However, as acknowledged by the respective authors, the above studies were somehow limited either by their retrospective design or by the lack of a control group . Furthermore, none of the studies assessed airway responsiveness in non‐responders experiencing symptoms during the test (ie SNRs), so the significance of milder AHR in this population remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The first showed that a large proportion of methacholine nonresponders who reported asthma-like symptoms developed overt asthma over a 3-year period (16). The second showed a marked improvement in symptoms and the disappearance of wheeze in methacholine non-responders receiving treatment with high doses of fluticasone (17).…”
Section: Discussionmentioning
confidence: 94%